Molecular dynamics simulations of the intrinsically disordered protein amelogenin. Issue 8 (11th June 2017) - Apicella, Alessandra; Marascio, Matteo; Colangelo, Vincenzo; Soncini, Monica; Gautieri, Alfonso; Plummer, Christopher J.G.
Abstract : Amelogenin refers to a class of intrinsically disordered proteins that are the major constituents of enamel matrix derivative (EMD), an extract of porcine fetal teeth used in regenerative periodontal therapy. Modifications in molecular conformation induced by external stresses, such as changes in temperature or pH, are known to reduce the effectiveness of EMD. However, detailed descriptions of the conformational behavior of native amelogenin are lacking in the open literature. In the present work, a molecular model for the secondary and tertiary structure of the full-length major porcine amelogenin P173 was constructed from its primary sequence by replica exchange molecular dynamics (REMD) simulations. The REMD results for isolated amelogenin molecules at different temperatures were shown to be consistent with the available spectroscopic data. They therefore represent an important first step toward the simulation of the intra- and intermolecular interactions that mediate self-organization in amelogenin and its behavior in the presence of other EMD components under conditions representative of its therapeutic application.